Faktor Sosiodemografis dan Sosioekonomi yang Berperan dalam Ketahanan Pangan Rumah Tangga Sangat Miskin Ekstrem di Wilayah Pesisir Demak - Aryani, Yovita; Mukson, Mukson; Legowo, Anang M (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Food is a fundamental necessity in our lives, yet many households face challenges in accessing sufficient and nutritious food, leading to food insecurity issues. The problem of food insecurity can occur even in food-producing areas, such as the coastal areas of Demak Regency. This research was undertaken to determine the sociodemographic and socioeconomic factors influencing poor household food security status in the coastal areas of Demak Regency. This study utilizes a survey-based approach, with sub-district samples selected purposively based on the highest number of poor households, as identified in the 2023 Targeting Data for the Acceleration of Extreme Poverty Eradication (P3KE) in Demak Regency. The sample areas included Sayung District and Bonang District. Household samples were chosen through multistage random sampling, resulting in a total of 104 households. Both primary and secondary data were used, collected through observation, literature study, and interviews using open and closed questionnaires. Data were analyzed employing multiple linear regression analysis performed with SPSS. The findings of the study show that the factors which have a significant influence (p<0.05) on food security conditions (Y) in poor households in coastal areas, namely: meat expenditure, rice expenditure, rice price, food expenditure share, meanwhile the factors that don't have significant influence (p>0.05) are mother' formal education, energy consumption level, and mother' age. The R² value of 0.689 means that approximately 68.9% of the variation in the dependent variable is explained by the independent variables in the regression model.